2006
DOI: 10.1111/j.1467-9280.2006.01685.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Exceptional Human Capital Over Two Decades

Abstract: Talent-search participants (286 males, 94 females) scoring in the top 0.01% on cognitive-ability measures were identified before age 13 and tracked over 20 years. Their creative, occupational, and life accomplishments are compared with those of graduate students (299 males, 287 females) enrolled in top-ranked U.S. mathematics, engineering, and physical science programs in 1992 and tracked over 10 years. By their mid-30s, the two groups achieved comparable and exceptional success (e.g., securing top tenure-trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(94 citation statements)
references
References 20 publications
(29 reference statements)
1
92
0
1
Order By: Relevance
“…These are children who are typically at or above the 95th percentile on standard intelligence (IQ) tests and are common in gifted and enrichment programs throughout the United States. Precocious children do well in academic settings (Lubinski, 2000;Walberg, 1984), will be over-represented among educated professionals in adulthood (Gottfredson, 1997), but, as a group, they differ in important ways from the mathematically gifted individuals studied by Lubinski et al (2006); the latter group includes individuals with estimated IQ levels found in only about 1 in 10,000 individuals. The "typical" intellectually precocious child is much more common, representing about 1 in 20 to 1 in 50 children.…”
Section: Mathematical Cognition In Intellectually Precociousmentioning
confidence: 99%
“…These are children who are typically at or above the 95th percentile on standard intelligence (IQ) tests and are common in gifted and enrichment programs throughout the United States. Precocious children do well in academic settings (Lubinski, 2000;Walberg, 1984), will be over-represented among educated professionals in adulthood (Gottfredson, 1997), but, as a group, they differ in important ways from the mathematically gifted individuals studied by Lubinski et al (2006); the latter group includes individuals with estimated IQ levels found in only about 1 in 10,000 individuals. The "typical" intellectually precocious child is much more common, representing about 1 in 20 to 1 in 50 children.…”
Section: Mathematical Cognition In Intellectually Precociousmentioning
confidence: 99%
“…Accordingly, the dominant operational definition of giftedness has long been based solely on measures of IQ (Callahan 2000;Tannenbaum 1996). Several longitudinal studies have proven that high intelligence is indeed a valid predictor of exceptional performance in professional life (Gottfredson 1997;Kuncel et al 2004;Lubinski et al 2006). In their longitudinal study of a group of students who had achieved exceptional SATs scores before the age of 13, Lubinski et al (2006) found that the same students, only 10 years later, had obtained an impressive list of achievements, including numerous scientific publications, inventions, and original contributions to literature and the arts.…”
Section: Intelligencementioning
confidence: 99%
“…Several longitudinal studies have proven that high intelligence is indeed a valid predictor of exceptional performance in professional life (Gottfredson 1997;Kuncel et al 2004;Lubinski et al 2006). In their longitudinal study of a group of students who had achieved exceptional SATs scores before the age of 13, Lubinski et al (2006) found that the same students, only 10 years later, had obtained an impressive list of achievements, including numerous scientific publications, inventions, and original contributions to literature and the arts. Kuncel et al (2004), in their meta-analysis, concluded that intelligence tests, specifically the Miller Analogies test, predict performance in graduate studies as well as job performance.…”
Section: Intelligencementioning
confidence: 99%
“…In another review, Sackett et al (2008) reported on several meta-analytic studies that found similar predictive results of GPA for all four years. In a longitudinal study of gifted children who took the SAT, results showed a positive relationship to getting a PhD, getting tenure, and having high job satisfaction, (Lubinski, Benbow, Webb, & Bleske-Rechek, 2006). There is also some indication for a positive relationship between the SAT and post college income and earnings (Bowen & Bok, 1998;Jenks & Phillips, 1998).…”
Section: The Sat As a Bad Predictormentioning
confidence: 99%